Assessment experiences in a math course - Soares, Filomena Baptista (2018)
The role of a teacher, as knowledge promoter and learning facilitator, is frequently opposed to the simultaneously inherent “validation” tasks, as far as grading and assessing are concerned, fundamentally from the students’ point of view, but, sometimes, even from our own. The generalised Math “trauma” is a difficult start-up invisible barrier that we must overcome every single semester, by implementing different strategies, developing new materials, motivating with digital and technological resources (using students’ digital skills), among many other tactics and schemes. But, in the end, the numerical grade – the knowledge and skills construction validation – must appear posted in the “system”. As Math lecturers in a Higher Education Institution, for more than twenty years, these problems are a daily challenge we face, and the issues we intend to analyse here, emerge as a consequence of a certain "emptiness" we feel regarding the assessment we have to carry out, in the sense that we still don’t have an answer to the following question: “Is it legitimate to "close your eyes" to the basic errors (some severe) when assessing learning outcomes in advanced subjects?” We teach at "end of the line", as far as General Mathematics is concerned, since our students are, essentially, from Management and Accounting Bachelor degrees. This paper will be structured in four distinct parts, starting with the Specific and General Outcomes and skills in the Math course in question, giving also a global vision of all its syllabus components and the teaching Methodologies implemented. Subsequently, we will refer to the coherence between teaching methods and the course learning objectives as well as their connection to the syllabus items. Finally, we will go through a section of small questions and answers, with their respective detailed analysis, in order to provide an objective reading material, trying to promote a fruitful and open discussion on the subject